Analisis Mekanisme Pelunasan Pembiayaan Murabahah di Bank Syariah Indonesia KCP Malang - Manan, Yuliyanti M.; Cholifah, Siti Nurul (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
This research aims to determine the conformity of the Fatwa DSN MUI No. 23/DSN/MUI/III/2002 regarding early settlement deductions and Fatwa No:46/DSN-MUI/II/2005 regarding Murabahah Billing Deductions in the mechanism of Murabahah financing settlement at BSI KCP Malang. In the settlement of Murabahah financing, customers can make payments before the due date or accelerate the settlement, and it can also be done according to the agreed-upon period (due date). However, in its implementation, there is still some ambiguity in Bank Syariah when providing discounts on the remaining selling price of Murabahah in settlements. Therefore, an analysis is needed in the practice of the Murabahah financing settlement mechanism at BSI KCP Malang in accordance with the DSN MUI fatwa. The research method used is qualitative research with an empirical or field research approach. Data collection techniques were obtained from the research object through observation, interviews, and documentation. The results of the research indicate that the Murabahah financing settlement mechanism carried out by BSI KCP Malang is in accordance with Fatwa DSN-MUI No.23/DSN/MUI/III/2002 and Fatwa No:46/DSN-MUI/II/2005. This can be seen from BSI's policy in settlement, where they provide discounts to customers who make payments on time or before the due date, and these discounts are not promised in the beginning. If customers inquire about discounts during the financing or before making the settlement, BSI KCP Malang does not explain the discount. However, if customers wish to settle, BSI KCP Malang will explain the discount or deduction given during the settlement.